MUSEUM OF THE FACULTY OF DENTISTRY - Barna Kelentey (Gerundium, 2022)
. In 2013, the Faculty of Dentistry (University of Debrecen) established a museum. The part of the museum, created primary, deals with the past of the faculty, documenting the establishment of its predecessor, the Stomatology Polyclinic, and later the Clinic itself. Its professors are ranged until the year 2000 and the textbooks and manuals in Hungarian-language are presented from 1871 to 1948. The world's first dental journal from 1839 and the first Hungarian-language newspaper from 1892 are also shown. Longstanding tools and instruments are correspondingly on display. Dental posters, recon bills and other old documents can also be seen. The glass-walled contemporary dental office, established in 2017, displays three classical dental units and machinery from the 1880s to the 1930s. A contemporary medical cabinet displays old tools, medications, and dental materials. On the wall besides the original poster, the medical diploma and the old photo, a medical caricature can also be seen. The museum principally collects contemporary dental tools and documents related to Hungary and holds only original resources. One of the largest dental museums in Hungary has been established over the years